Analyzing The Evolution of Environmental Literacy Research in 21st Education: A Bibliometric Analysis from 2001 to 2022 - Dwiputra, Dimas Febriansyah Krisna; Maryani, Enok; Susanti (Indonesian Journal of Educational Research and Review, 2024)
Environmental literacy has emerged as a paramount subject to be studied and ingrained in individuals in the 21st century due to the rising concerns over environmental problems. Hence, this research is aimed at analyzing the development of environmental literacy topics in the educational context in the 2001-2022 period to understand the development and potential of this research in the future. This study used the bibliometric analysis method with data sourced from Scopus. Out of 518 articles obtained, only 386 met the criteria for performance analysis and scientific mapping using Publish or Perish and VoSViewer software. The result showed that the development of environmental literacy in the educational context has increased both in terms of publication productivity and the number of citations. The United States, Indonesia, and Turkey contributed the most. Although overall the issues raised are still dominated by environmental literacy and environmental education, there has been a shift in the last three years. The result of this study indicates that the subject of environmental literacy within educational settings remains both compelling and pertinent for future exploration. These findings have implications for the urgency of expanding the scope of environmental literacy research in the educational context to issues that are still limited. Consequently, this study can serve as a roadmap for researchers to establish new research directions, enrich existing knowledge, and make a more substantial contribution to developing environmental literacy in educational contexts in the 21st century.